2012
DOI: 10.5897/ajmr12.155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of land use system on Arbuscular Mycorrhiza fungi in Maasai Mara ecosystem, Kenya

Abstract: Arbuscular mycorrhiza fungi (AMF) diversity and inoculums potential were assessed in different land use systems (protected and unprotected grassland and woodland, intensified monocropping systems and subsistence farming systems) in dry and wet region of Maasai Mara ecosystems (MME) during dry and wet season (November, 2009 and April, 2010). AMF spore were assessed in field and trap cultures (sorghum) using morphological tools. AMF inoculums potential were assessed using undisturbed soil cores planted with sorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
2
4
2
Order By: Relevance
“…The six AMF genera identified in this study were present in all the AEZs and CTs but differences in their spore production were not significant. The AMF genera observed in this study were lower than 12 isolated in Sudan (76), 15 in Ethiopia (24), 15 in Southern China (77), 9 in Ethiopia (73) but higher than the 4 to 5 genera isolated in Kenya (23,28,34) and 4 in Rwanda (78). This may be due to variances in edaphic conditions and the cropping systems of the study sites.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…The six AMF genera identified in this study were present in all the AEZs and CTs but differences in their spore production were not significant. The AMF genera observed in this study were lower than 12 isolated in Sudan (76), 15 in Ethiopia (24), 15 in Southern China (77), 9 in Ethiopia (73) but higher than the 4 to 5 genera isolated in Kenya (23,28,34) and 4 in Rwanda (78). This may be due to variances in edaphic conditions and the cropping systems of the study sites.…”
Section: Discussioncontrasting
confidence: 51%
“…Similarly, the dominance of Scutellospora and Acaulospora had been reported earlier in Western Kenya (29). Sporulation of genus Acaulospora was high in acidic soils (26,30), increasing their dominance in soils of a pH range of 5.51 to 6.77 (28). Castillo et al (31) reported high sporulation of Acaulospora spp.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations